Passivity and electrocatalysis of nanostructured nickel encapsulated in carbon - Haslam, Gareth E.; Chin, Xiao-Yao; Burstein, G. Tim (Physical chemistry chemical physics : PCCP, 2011)
Metallic nickel is a powerful electrocatalyst in alkaline solution and is able to be used in the alkaline fuel cell. However, in acidic solution, electrocatalysis is impossible because the metal is subject to rapid corrosion at low pH for all potentials at which an acidic fuel cell would operate. Here we report the synthesis and passive nature of a nickel-carbon nanostructured material which shows electrocatalytic activity. A thin film composed of nickel and carbon prepared by co-sputtering a graphite target partially covered with a nickel foil shows remarkable passivity against corrosion when polarized in hot sulphuric acid. The film, which contains 21 atom-% nickel, also shows significant electrocatalysis of the hydrogen oxidation reaction, and therefore forms the basis of a new type of fuel cell anode catalyst. High-resolution transmission electron microscopy (HRTEM) reveals a nanostructure of carbon-encapsulated nickel nanocrystals of ≤ca. 4 nm diameter. The passive nature of the material against corrosion is due to protection generated by the presence of a very thin carbon-rich layer encapsulating the nanoparticulate catalyst: this is a new form of passivation.